Fabrication and Cytocompatibility Evaluation of Psyllium Husk (Isabgol)/Gelatin Composite Scaffolds - Poddar S.; Agarwal P.S.; Sahi A.K.; Vajanthri K.Y.; Pallawi; Singh K.N.; Mahto S.K. (My University, 2025)
Psyllium husk or isabgol contains xylan backbone linked with arabinose, rhamnose, and galacturonic acid units (arabinoxylans). In this study, we demonstrate the fabrication and characterization of a macroporous three-dimensional (3D) composite scaffold by mixing psyllium husk powder (PH) and gelatin (G) in different ratios, viz.100 PH, 75/25 PH/G, and 50/50 PH/G (w/w), using an EDC-NHS coupling reaction followed by freeze-drying method. The reaction was performed in aqueous as well as in alcoholic media to determine the most appropriate solvent system for this purpose. The mechanical strength of the scaffold system was improved from 151 to 438 kPa. The fabricated scaffolds exhibited enhanced structural stability, remarkable swelling capacity, and escalated cell growth and proliferation. ATR-FTIR analysis showed the presence of amide and ester bonds indicating covalent crosslinking. SEM micrographs revealed the porous nature of the scaffolds with pores ranging from 30 to 150 μm, and further pore size distribution curve indicated that 75/25 PH/G (w/w%) EDC-NHS-alcohol scaffold exhibited the best fit to the Gaussian distribution. Swelling capacity of the 100 PH EDC-NHS-alcohol scaffolds was found to be nearly 40% from its original weight in 48 h. MTT assay using fibroblast cells revealed ~ 80% cellular proliferation by 6th day within the fabricated scaffolds in comparison to control. [Figure not available: see fulltext.]. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.